Inoculation of IAA producing endophytic bacteria on the growth of mung bean (Vigna radiata L.) Var. vima2 - Fauzi Akhbar Anugrah; Desi Yulia Safitri (Universitas Negeri Malang, 2018)
The interaction of endophytic bacteria with their host plants through a direct mechanism can stimulate growth by increasing nutrient absorption and modulating phytohormones such as IAA (Indole-3-acetic acid). A previous study revealed the IAA production ability by endophytic bacteria from Cinchona (Cinchona Iedgeriana Moens.) plant. The most optimum IAA producer from the previous study will be analyzed for the effect on plant growth. The purpose of this study was to test and analyze the effect of IAA-producing endophytic bacteria inoculation obtained from the roots of cinchona on the growth parameter of mung bean seedling. The highest IAA-producing bacteria, isolate with code a15 has been compared to the MC Farland 0.5 and MC Farland 1 standards are used to soak the mung bean seeds for 1 hour and being planted on sterile soil media in six replications. The inoculation of MC Farland 0.5 equivalent bacteria showed the increased growth parameters of mung bean seedling, such as height, wet weight, and the number of leaves. Furthermore, the concentration of bacterial suspension that has been equalized with the Mc Farland 1 shows the inhibition effect of the growth.